Quality control and diagnostic efficiency of bovine ppd (tuberculin) from indigenous Mycobacterium bovis - GARGI, AKSHAY; VERMA, RISHENDRA (The Indian Journal of Animal Sciences, 2011)
Purified protein derivative (PPD) tuberculin was prepared from Mycobacterium bovis 3/86 and 4/86 strains isolated from Indian cattle. These M. bovis strains were harvested in bulk by growing them in Dorset Henley's liquid medium. PPD of M. bovis AN5 from Veterinary Laboratory Agency, Surrey, UK, was used as control. The PPD produced from M. bovis (3/86 and 4/86) were standardized by conforming to sterility, safety and potency in guinea pigs as per standard. AU the 3 PPD preparations subjected to 12% polyacrylamide gel electrophoresis (SDS-PAGE) showed smearing along with 2 distinguished bands of 20-22 kDa. In 2-D electrophoresis, in first-dimension IEF by IPG strips, distinct banding patterns were not identified in PPD tuberculin's, in second din1ension, there were distinct spots in acidic positions as well as in basic position in PPD M. bovis 3/86. DTH response with PPD M. bovis (3/86 and 4/86) w'as significant at 72h post-inoculation of tuberculin. There was no significant variation (PÂ